Design of Digital IFE and EFE Evaluation of A3N 766HI Organic Fertilizer Products to Make Strategic and Sustainable Decisions - Silalahi, Amin (Universitas Nusantara PGRI Kediri, 2024)
Research aim: to answer the question,